2001
DOI: 10.1002/1521-3757(20011217)113:24<4881::aid-ange4881>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Total Synthesis of (±)-Galanthamine

Abstract: Durch eine intramolekulare Heck‐Reaktion von 3 wird ein quartäres Spiro‐C‐Atom generiert – der Schlüsselschritt einer effizienten Synthese von Galanthamin 1. In den letzten Stufen der Synthese wird 1 aus dem tricyclischen Dienon 2 erhalten, das durch eine nichtklassische Dehydrierungsmethode aus dem entsprechenden α,β‐ungesättigten Keton hergestellt wurde.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Galanthamine is produced on a large scale from Bulgarian Leucojum aestivum [4] and also by chemical synthesis [5][6][7]. However, the synthesis is complicated and time consuming because galanthamine has three asymmetric carbons requiring stereochemically controlled synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Galanthamine is produced on a large scale from Bulgarian Leucojum aestivum [4] and also by chemical synthesis [5][6][7]. However, the synthesis is complicated and time consuming because galanthamine has three asymmetric carbons requiring stereochemically controlled synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…For medical applications, it is obtained via a low-yielding and complex total synthesis (Guillou et al 2001;Marco-Contelles et al 2006), but it has also been isolated from Leucojum aestivum bulbs in particular (Berkov et al 2005). A number of studies have reported that Gal is accumulated in Amaryllidaceae tissue cultures and that some factors can enhance its accumulation (Selles et al 1997;Colque et al 2004;Diop et al 2007;Diop et al 2006;Ptak et al 2009;Georgiev et al 2009;Berkov et al 2009a, b;Ptak et al 2010), suggesting that biotechnological methods can be considered as an alternative approach for the production of this alkaloid.…”
Section: Introductionmentioning
confidence: 99%
“…The two main commercial sources of galanthamine are organic synthesis and plant extraction; the first one is low yielding and complex [12,13], the second is limited by several factors: the low concentration of galanthamine in plants (variation from trace to 0.5% [14]), seasonal variation [15]. Besides, overharvesting is causing depletions of wild Amaryllidaceae populations [16].…”
mentioning
confidence: 99%